Tanggung Jawab Kurator Terhadap Penjualan Harta Pailit Jaminan Debitur PT Bank Rakyat Indonesia Agroniaga Tbk KC Pekanbaru (Studi Kasus Kepailitan Koperasi Karyawan Nusantara Lima) - Richad Sahat Silitonga (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
Proof of the responsibility of the curator in the sale of bankrupt assets based on the Bankruptcy case decision Number: 08 / Pdt.Sus-PKPU / 2015 / PN-Niaga Medan is unclear, because in the decision there is no explanation of the witness evidence submitted by the applicant or the respondent. So in the case of proof it has been legally flawed and violated Article 163 point b Herzein Indonesis Reglement (H.I.R), Article 184 points b Buitengewesten  Rechtsreglement  (RBg)  and Article  1866  points  b  Civil  Code  (KUH Perdata). In this ruling the author examines the lack of evidence that states the Respondent of the five archipelago employee cooperatives which were declared bankrupt by the Medan Commercial Court. Legal considerations by the panel of judges against the curator in the sale of bankrupt assets based on the PKPU case verdict Number: 08 / Pdt.Sus-PKPU / 2015 / PN.Mdn are inaccurate, because the decision of the panel of judges did not explain the duties of a curator in the sale of bankrupt assets which will cause a loss to the curator himself. So in this case illustrates that a judge does not carry out his duties as stipulated in Article 184 Herzein Indonesis Reglement (H.I.R).